2011
DOI: 10.1002/ajh.22126
|View full text |Cite
|
Sign up to set email alerts
|

Utility of positron emission tomography scans in mantle cell lymphoma

Abstract: Positron emission tomography (PET) scans are widely used in patients with lymphoma but little is known about their utility in mantle cell lymphoma (MCL). MCL patients were included from two prospective trials and one observational study at our institution. A total of 276 PET scans were performed among 52 patients. After a median follow-up of 37.5 months, the 3-year event-free survival (EFS) and overall survival (OS) were 73% (95% confidence interval [CI]: 61-85%) and 92% (95% CI 85-100%), respectively. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
(50 reference statements)
3
32
0
3
Order By: Relevance
“…Likewise, another retrospective study found 18 F-FDG PET useful to predict PFS at 1 y in patients with MCL receiving rituximab and cytarabine-or anthracycline-based therapies (18). A third retrospective review of 28 available end-of-treatment scans (all in patients receiving rituximab-containing treatment) did not observe a statistically significant association between CMR and 3-y survival; however, no deaths were reported among patients with negative end-of-treatment scans, making a trend for better OS but not 3-y event-free survival (25). Similarly, a retrospective analysis of posttreatment 18 F-FDG PET scans for patients with MCL initially treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone found no differences in OS or PFS at 3 y between patients with positive and negative scans (26).…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, another retrospective study found 18 F-FDG PET useful to predict PFS at 1 y in patients with MCL receiving rituximab and cytarabine-or anthracycline-based therapies (18). A third retrospective review of 28 available end-of-treatment scans (all in patients receiving rituximab-containing treatment) did not observe a statistically significant association between CMR and 3-y survival; however, no deaths were reported among patients with negative end-of-treatment scans, making a trend for better OS but not 3-y event-free survival (25). Similarly, a retrospective analysis of posttreatment 18 F-FDG PET scans for patients with MCL initially treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone found no differences in OS or PFS at 3 y between patients with positive and negative scans (26).…”
Section: Discussionmentioning
confidence: 97%
“…MCL is a PET-positive tumor; however, PET scanning does not reliably detect bone marrow or bowel disease and therefore does not add to conventional staging. 71,72 In 3 large studies involving patients treated with different regimens, a positive PET scan did not predict for an inferior OS when used either as an interim assessment or at the end of therapy. 71,73,74 One of these studies did show a significant difference in PFS following a positive PET at the completion of therapy, 74 and 1 other smaller study found a positive post-therapy scan was more likely to predict for relapse.…”
Section: Stratified Approachesmentioning
confidence: 97%
“…71,72 In 3 large studies involving patients treated with different regimens, a positive PET scan did not predict for an inferior OS when used either as an interim assessment or at the end of therapy. 71,73,74 One of these studies did show a significant difference in PFS following a positive PET at the completion of therapy, 74 and 1 other smaller study found a positive post-therapy scan was more likely to predict for relapse. 72 When used for surveillance, a high false-positive rate (35%) has been reported, 71 and in 2 studies where surveillance was assessed, it was concluded that PET scanning did not meaningfully contribute.…”
Section: Stratified Approachesmentioning
confidence: 97%
See 2 more Smart Citations